Managerial Performance Relation to Environmental Uncertainty and Utilization of Management Accounting Systems: A Literature Study - Ambarriani, Anastasia Susty; Syifaudin, Ahmad; Mayndarto, Eko Cahyo; Nugraha, Erik (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to understand the uncertainty of the company's business environment and the use of management accounting systems as a form of application of information and communication technology to managerial performance. Various obstacles, difficulties, and obstacles were encountered in running the company's operations. One of them is environmental uncertainty. Environmental uncertainty is a circumstance that firm management must strive to keep to a bare minimum. A management accounting system will be implemented as a result of the efforts to eliminate environmental uncertainty, which will be a significant step forward in the effort to overcome environmental uncertainty. Managers' management accounting system is to be more active in searching for data related to the processes they carry out, so this encourages managers to be more active in carrying out processes, coordination, monitoring, and evaluation. In this study, a qualitative descriptive technique was used to collect information. In this study, a literature review strategy was taken in order to gather information for the study. The results show that from 10 previous studies, both national and international, adding that the application of management accounting is one of the efforts made by company management to minimize uncertainty and the environment. The application of a management accounting system that is supported by technology in the company can provide high quality and useful information to increase the effectiveness of company managers in making fast, relevant and accurate decisions to solve company problems due to current or future uncertainties as well as to survive and be able to compete in a competitive business environment. Therefore, it can be seen that one way to minimize environmental uncertainty is to implement a management accounting system to improve managerial performance.